Surface Micro-Reflector Array for Augmented Reality Display - Zhanjun Yan; Chunlei Du; Lixin Zhang (IEEE Photonics Journal)
Geometric optical waveguide display can significantly miniaturize the augmented reality eyeglasses, but suffers from the ghost image. In this paper, a method using surface micro-reflector array is proposed, which can dramatically suppress the ghost image. The transmission and expansion of the light bearing image are completed by using planar waveguide and micro-reflector array embedded in the surface layer of waveguide. The image quality is improved by using the dual channel to eliminate ghost image. The imaging process of optical system is modeled and simulated. The surface micro-reflector array waveguide element of 3 mm thickness is prepared for verification. The whole optical system has the advantages of simple structure, easy preparation and high structural strength. The display field of view is shown to be 25° × 25°, and the size of the full field of view area is 15 mm with even light distribution. What's more, the uniformity of imaging intensity is better than 20%, and the image is clear without ghost image, which can effectively realize the fusion of the virtual image and the real environment. Thus, the efficiency of augmented reality is greatly improved, and the danger of human eye safety is effectively avoided.